(untitled) (Research, Society and Development, 2019)
This paper seeks briefly to discuss the conception of Professional Education and human formation, in the stage corresponding to the current High School, within the historical cuts, that correspond to the decade of 1970 of the twentieth century, until the present days of the 21st century, which in this chronological analysis, The aim of this study is to analyze the reverberations that educational policies promoted in Brazilian school education focusing on Professional Education, especially with the enforcement of Law No. 5.692/1971, which instituted compulsory vocational training in 2nd grade education, under Decree No. 2.208/1997, which determined the compulsory separation between High School and Professional Technical Education at the secondary level, Decree 5,154/2004, which repealed Decree 2.208/1997 and brought the possibility of integration between secondary and vocational technical education at secondary and intermediate levels, starting in 2017, when the new high school reform was instituted through Law No. 13,415 / 2017 and its supplementary standards, in the reflective sense of the paths taken by education in its political conjuncture a brief review aligned with an analysis of bibliographical and documentary research. It is a determining factor to consider the Brazilian Education with the role of the National Congress and the policies promoted by these agents. In this direction, it has been historically perceived that the relationship between Professional Education and Basic Education has been weakened by polemics and conflicts of interest, especially in relation to the relations between technical courses of middle level and the last stage of basic education, namely: the current High School. Therefore, it is worth noting that we understand professional education, not only as a teaching modality but, above all, as an area of scientific knowledge that is still little explored, characterized by tensions and discussions historically located within social, political, economic and cultural aspects.